The role of technology in shaping the coexistence of local hospital buildings - Abdullatief AL Taie Huda; Hasan Hashim Almajidi Basim; Hashim Hameed El-Eqapy Ahmed (BIO Web of Conferences, 2024)
Architecture is one of the reflections of the development of societies and an indication of the extent of their development from the technological aspect, as this results in products characterized by uniqueness and positivity, as the role of technology is highlighted in the occurrence of symbiotic interference on existing buildings, especially hospital buildings, because this type of building has a constant need for expansion, so the relationship between the origin and the symbiont differs. Depending on the time of addition and the subsequent technological developments that give possibilities and possibilities for coexistence, in addition to the factor of the surrounding environment, the general fabric, and the original building, the important role in determining patterns for reconfiguration of coexistence. However, the concept of technology has the fundamental role in determining the type of relationship and connection and its degree between two cities, as the research aims to clarify the perception. Knowledge about the impact of technology on existing local hospital buildings in terms of materials, structures and mechanisms used when merging old and new, and applying the theoretical framework that has been reached on two samples of existing local hospitals and showing how to achieve the coexistence formation of this type of building to arrive at the most important conclusions (developments affect Technology on hospital configurations when adding and expanding, especially at the levels (structures - materials - facades - basic composition)).